Could Estradiol be used as a biomarker of infection in Schistosoma haematobium infected patients? - Botelho, M.C (2017)
Urogenital schistosomiasis is a chronic infection caused by the human blood fluke Schistosoma haematobium. Schistosomiasis haematobia is a known risk factor for cancer leading to squamous cell carcinoma of the urinary bladder (SCC). This is a neglected tropical disease endemic in many countries of Africa and the Middle East. Schistosome eggs produce catechol-estrogens. These estrogenic molecules are metabolized to active quinones that cause alterations in DNA (leading in other contexts to breast or thyroid cancer). Our group has shown that schistosome egg associated catechol estrogens induce tumor-like phenotypes in urothelial cells, originated from parasite estrogen-host cell chromosomal DNA adducts and mutations. Also we have demonstrated that these molecules are detected as Estradiol in sera of infected patients.